Validation of the qSOFA score compared to the CRB-65 score for risk prediction in community-acquired pneumonia. (September 2021) - Kesselmeier, Miriam; Pletz, Mathias W.; Blankenstein, Anna Leona; Scherag, André; Bauer, Torsten; Ewig, Santiago; Kolditz, Martin
Abstract: Objective: The qSOFA (quick sepsis-related organ failure assessment) score shows similarities to the CRB-65 pneumonia score, but its prognostic accuracy in patients with community-acquired pneumonia (CAP) has not been extensively evaluated. Our aim was to validate the qSOFA (-65) score in a large cohort of CAP patients. Methods: We conducted a retrospective population-based cohort study including all CAP cases hospitalized between 1st January 2014 and 31st December 2018 from the German nationwide mandatory quality assurance programme. We excluded cases transferred from another hospital, with mechanical ventilation present on admission, and without documented respiratory rate. Predefined outcomes were hospital mortality and need for mechanical ventilation. Results: Among the 1, 262, 250 included cases, hospital mortality was 12.4% and the mechanical ventilation rate was 7.1%. All CRB and qSOFA criteria were associated with both outcomes, but the qSOFA had inferior sensitivity compared to the CRB-65 for mortality prediction. Including the age criterion ≥65 years, qSOFA-65 and CRB-65 performed similarly (AUC 0.69, 95%CI 0.69–0.69 versus 0.68, 95%CI 0.68–0.68). A qSOFA-65 of 0 was associated with fewer missed deaths (3328, 2.0%) compared to a CRB-65 of 0 (5480, 2.4%). The sensitivity of the suggested qSOFA cut-off of ≥2 for sepsis was low (mortality 25.8%, 95%CI 25.6–26.0%; mechanical ventilation 24.1%, 95%CI 23.8–24.4%). Results were similar when frail and palliative patients were excluded. Conclusions: The qSOFA parameters show prognostic accuracy similar to the CRB parameters in CAP, but the sepsis cut-off of ≥2 lacked sensitivity. For sensitive mortality prediction, the age criterion ≥65 years should be added to the qSOFA.